Study of the effect of mechanical impact parameters on an impact-mode piezoelectric ceramic power generator - Basari, Amat Amir; Sosuke, Awaji; Shintaro, Sakamoto; Seiji, Hashimoto; Bunji, Homma; Kenji, Suto; Hiroaki, Okada; Hideki, Okuno; Kojiro, Kobayashi; Shunji, Kumagai (2015)
This paper presents an analytical and experimental study on the effect of mechanical impact parameters on impact-mode piezoelectric ceramic power generators. The parameters are the velocity and mass. The method of analysis is based on a weight drop experiment. The results show that the peak of the instantaneous output voltage is proportional to the impact velocity, and for the output power, it is in a straight line relationship with the same parameter. For the same velocity of impact, the advantage of using heavy objects is clear because its momentum and the impact force are higher. However, an adjustment in the velocity of impact is found to be more effective for higher instantaneous output power than the mass. This finding is supported by the output power that is generated by a 4-g steel ball with a momentum of 4.34 gm/s, which is almost 300% higher than that of an 8-g steel ball for the same momentum. The frequency responses of a vibration-based impact-mode piezoelectric ceramic power generator also support the same conclusion.